Głosy nieważne w elekcjach samorządowych - Ptak, Arkadiusz (Przegląd Politologiczny, 2018)
Invalid votes in local government elections in Poland, in particular at the regional level, are among the most pressing problems of the electoral process. The number of invalid votes is so large that it serves political conflict in which accusations of election fraud are formulated. These are scarcely justified, though, since over 70% of invalid votes in local parliament elections lack an “x” next to the name of any candidate (rather than the addition of another “x” on the ballot). The analysis of this issue indicates that the reason for such a high percentage of invalid votes can be found in some elements of the electoral system. Large constituencies, sometimes of up to a dozen districts, mean political parties marginalize the smallest units (i.e. rural and urban-rural communities) when drawing up electoral lists and running election campaigns. The candidates on electoral lists for local parliaments very rarely come from rural regions, which does not stimulate the interest of their citizens in elections at this level. Consequently, it is the rural and urban-rural communities that have the largest proportion of invalid votes, accounting for 17.13% and 14.50% respectively. The number of invalid votes in the units which submit the largest number of candidates, that is in urban communities, amounts to 7.19% (such a low percentage results from the fact that no elections are run for county councils in towns with county status as city councils operate at this level of authority). These elements of the electoral system are not the only reasons for the phenomenon of invalid votes. It is also encouraged by Poles’ low civic consciousness and their ignorance of fundamental democratic mechanisms, including the principles of electoral law.